Long-term safety of aclidinium bromide/formoterol fumarate fixed-dose combination: Results of a randomized 1-year trial in patients with COPD. (July 2016) - Donohue, James F.; Soong, Weily; Wu, Xiao; Shrestha, Pomy; Lei, Alejhandra
Abstract: Trial design: This was a one-year, Phase III randomized, double-blind, parallel-group, active-control study investigating the long-term safety and tolerability of twice-daily aclidinium 400 μg/formoterol 12 μg versus formoterol 12 μg. Methods: Eligible patients were male or female, current or ex-smokers (history of ≥10 pack-years) aged ≥40 years with a diagnosis of moderate to severe chronic obstructive pulmonary disease (COPD): post-bronchodilator forced expiratory volume in 1 s (FEV1 )/forced vital capacity (FVC) ratio <70%, and post-bronchodilator FEV1 ≥30% and <80% predicted. Patients were randomized 2:1 to twice-daily aclidinium 400 μg/formoterol 12 μg or formoterol 12 μg, administered via a multidose dry powder inhaler (Genuair™/Pressair ® ) 1 . The objective was to evaluate the one-year safety of aclidinium 400 μg/formoterol 12 μg versus formoterol 12 μg. Results: All 590 patients were included in the safety population; 392 patients received aclidinium 400 μg/formoterol 12 μg and 198 patients received formoterol 12 μg. Of these, 581 patients were included in the intent-to-treat (ITT) population (385 patients received aclidinium 400 μg/formoterol 12 μg; 196 patients received formoterol 12 μg). In the safety population, the percentage of patients with ≥1 treatment-emergent adverse event was similar between aclidinium 400 μg/formoterol 12 μg (71.4%) and formoterol 12 μg (65.7%). Mean baseline post-bronchodilator FEV1 was 51.3% of predicted (ITT population). Aclidinium 400 μg/formoterol 12 μg significantly improved morning pre-dose (trough) FEV1 and trough FVC versus formoterol 12 μg at each assessment, with improvements at Week 1 (least squares mean difference [LSMD]: 87.4 mL and 157.8 mL, respectively) maintained at study end (LSMD: 81.5 mL and 185.4 mL, respectively). Conclusions: Aclidinium 400 μg/formoterol 12 μg was well tolerated, with a safety profile similar to formoterol 12 μg and consistent with that seen in two Phase III studies. Additionally, aclidinium 400 μg/formoterol 12 μg improved lung function versus formoterol 12 μg, with a sustained effect over one year. Highlights: Phase III study of the long-term safety of aclidinium bromide/formoterol fumarate. Patients randomized to BID aclidinium 400 μg/formoterol 12 μg or formoterol 12 μg. Aclidinium/formoterol was well tolerated and similar to monotherapy. The safety profile was consistent with that seen in two Phase III studies. Lung function was improved versus monotherapy and sustained over one year.